GENEALOGI PEMALSUAN DAN OTOPSI OTORITATIF: EVOLUSI PARADIGMA KRITIK HADITS MAUDHU’ DARI ERA KLASIK HINGGA EKOSISTEM DIGITAL - Ibnu Khotim; Sriyono Fauzi (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
This study aims to reconfigure the verification paradigm of scholars regarding fabricated hadith and its significance in navigating the digital information dissemination ecosystem. The existence of hadith fabrication has long manifested as an epistemological anomaly since the formative period of Islam, rooted in politico-sectarian fragmentation. Employing a qualitative approach with a historical-critical paradigm and content analysis, this research discourses on the instruments of al-jarh wa al-ta'dil and naqd al-matn constructed by classical scholars, alongside their adaptation by contemporary academics. Empirical findings confirm that the scholars' episteme transcends sanad verification, integrating textual rationality criticism (dirayah) and linguistic anomaly detection. Within the cybernetic context, the challenge metamorphoses into algorithmic dissemination virality on social media, which marginalizes the principle of tabayyun. In conclusion, the synthesis of classical methodology and digital-technological literacy is an absolute prerogative to safeguard the authority of the Prophetic Sunnah from ideological manipulation.